Morphological and ITS-based phylogenetic assessment of Euphorbia sect. Pithyusa (Euphorbiaceae) in Türkiye with taxonomic notes - Özcan, Taner; Genç, İlker; Kültür, Şükran; Ecevi̇t-Genç, Gülay; Di̇rmenci̇, Tuncay (Phytotaxa, 2026)
15 species of Euphorbia sect. Pithyusa are distributed in Türkiye. In this study morphological and molecular analyses were conducted on these taxa which is a study covering all Turkish species of the section Pithyusa. ITS-based phylogenetic analyses conducted in this study, which included a total of 129 samples, clearly elucidated the evolutionary relationships among the studied taxa and enabled a more robust interpretation of species-level boundaries. A diagnostic key was prepared using morphological characters as determined through comprehensive field and herbarium investigations. Phylogenetic analyses of Euphorbia pestalozzae, E. pisidica, E. yildirimlii and E. falcata subsp. macrostegia was done for the first time in this study. Euphorbia cassia, E. thessala and E. terracina, which have previously been studied from different countries, were analysed for the first time in this study for Turkish samples. Seed surface characteristics aligned with phylogenetic groupings based on nrITS data examined in this study, those with smooth and non-smooth seed surfaces were in different clades, though E. petrophila, despite its pitted seed surface, deviated from this general morphological-phylogenetic correlation. It has been revealed that Turkish endemics E. pestalozzae and E. pisidica are closer to E. cheiradenia than to E. petrophila. Extensive fieldwork across the distribution range of Euphorbia falcata, with emphasis on subsp. macrostegia, revealed distinct morphological features separating it from other infraspecific taxa. Nuclear DNA sequence analyses formed a well-supported clade corresponding to subsp. macrostegia, indicating clear genetic divergence. Based on this evidence, the subspecies warrants elevation to species rank. We propose the new name Euphorbia bornmuelleri, recognizing its distinct evolutionary lineage within the complex. Morphological and micromorphological analyses indicate that Euphorbia yildirimlii, described in 2012, closely resembles E. macroclada. Molecular data support this resemblance, so it was decided that E. yildirimlii is a synonym of E. macroclada.